Edupreneurship implementation through teaching factory on mechanical engineering competence - Tri Kuat; Purnawan Purnawan (Jurnal Pendidikan Vokasi, 2022)
This study aims to (1) Describe how the edupreneurship implementation through Teaching Factory (TEFA) on the mechanical engineering expertise competence at SMK Muhammadiyah 1 Sukoharjo; (2) Describe the factors supporting the successful implementation of edupreneurship through teaching factory on the mechanical engineering expertise competence at SMK Muhammadiyah 1 Sukoharjo; and (3) Describes the contribution of the edupreneurship implementation through the teaching factory in fostering an entrepreneurial spirit in mechanical engineering students at SMK Muhammadiyah 1 Sukoharjo. This qualitative research used a descriptive approach. The data were collected by interview, observation, and documentation. The informants comprised principals, vice-principals of curriculum, heads of engineering expertise programs, productive teachers, and students. The data analysis technique employed interactive analysis techniques, starting from data collection and then the data were reduced; after being reduced, the data were presented, and the last was verification. The data validity was then tested by triangulation of sources. The findings in this study revealed that (1) In terms of planning, organizing, implementing, and monitoring/evaluating, the edupreneurship implementation through teaching factory on the mechanical engineering expertise competence at SMK Muhammadiyah 1 Sukoharjo has been going very well by producing medical device products, especially patient beds that were produced and have been marketed to PKU Muhammadiyah Hospital in Central Java; (2) The factors driving the success of edupreneurship through technology factory comprised: quality educator resources, adequate infrastructure both in quantity and quality, standard operating procedures according to industry standards, quality products, and a well-established product marketing network; and (3) The edupreneurship implementation through the teaching factory contributes to fostering an entrepreneurial spirit by directly involving students in planning, production, and marketing.